Manufacturer’s Business Strategy: Interaction of Sharing Economy and Product Rollover - Jian Feng; Bin Liu; Zhenfeng Liu (Complexity)
This paper develops an analytical framework to study a manufacturer’s optimal business strategy involving the interaction of product sharing and product rollover in the sharing economy. Our analysis reveals that, regardless of whether the production cost is high or low, the manufacturer will participate in product sharing as long as the new product’s rental cost is not very high. Furthermore, under the manufacturer’s participation in product sharing, the manufacturer will sell two generations of products when the production cost is low. When the production cost is moderate, the manufacturer will adopt single rollover. Finally, the manufacturer’s participation in product sharing will increase the old/new product’s price and the manufacturer’s total profits but will decrease the old/new product’s demand in the sales market. Meanwhile, the manufacturer’s product sharing will decrease the price and demand of idle products from owners in the sharing market.